2010
DOI: 10.3390/ijms11093149
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for DNA Extraction from Mature Date Palm Leaves: Impact of Sand Grinding and Composition of Lysis Buffer

Abstract: Molecular marker techniques have been widely used for cultivar identification of inbred date palms (Phoenix dactylifera L.; Arecaceae) and biodiversity conservation. Isolation of highly pure DNA is the prerequisite for PCR amplification and subsequent use such as DNA fingerprinting and sequencing of genes that have recently been developed for barcoding. To avoid problems related to the preservation and use of liquid nitrogen, we examined sterile sand for grinding the date palm leaves. Individual and combined e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 16 publications
1
48
0
4
Order By: Relevance
“…The values of 260/230 OD ratio for pure nucleic acid were often higher than the respective 260/280 OD ratio values 31 . We found that the ratio at 260/230 nm wasabove 2.0, which confirmedthe extracted DNA to be of good quality 30 . Lower ratios may indicate the presence of phenols, aromatic compounds, peptides and carbohydrates contaminants which absorb near 230 nm 29,32 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The values of 260/230 OD ratio for pure nucleic acid were often higher than the respective 260/280 OD ratio values 31 . We found that the ratio at 260/230 nm wasabove 2.0, which confirmedthe extracted DNA to be of good quality 30 . Lower ratios may indicate the presence of phenols, aromatic compounds, peptides and carbohydrates contaminants which absorb near 230 nm 29,32 .…”
Section: Discussionsupporting
confidence: 52%
“…In our study, the 260/280 OD ratio wasabove of 1.8 and less than 2.0; indicating the extracted DNA to be free from protein and RNA contaminations ( Table 2). A secondary measure of nucleic acid purity was based on the 260/230 OD ratio 26,30 . The values of 260/230 OD ratio for pure nucleic acid were often higher than the respective 260/280 OD ratio values 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of liquid nitrogen to macerate leaf tissue is advantageous because it allows rapid freezing and as a result, it avoids DNA degradation (DANNER et al, 2011). However, attainment, cost, and storage are the obstacles for its use in many laboratories (IBRAHIM et al, 2010;IHASE et al, 2016), such as those located in the Amazon.…”
Section: Resultsmentioning
confidence: 99%
“…These factors limit the routine use of liquid nitrogen in many laboratories, including those located in the Amazon. Several studies have investigated alternative methods to macerate leaflets, especially in fibrous palms (IBRAHIM et al, 2010;IHASE et al, 2016). Ibrahim et al (2010) used sterilized sand with buffer to macerate mature leaves of date palm (Phoenix dactylifera).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation